Antipsychotikaassoziierte motorische Symptome bei schizophrenen Psychosen: Teil 2 : Katatone Symptome und malignes neuroleptisches Syndrom = Antipsychotic-inducedmotor symptoms in schizophrenic psychoses : Part 2 : Catatonic symptoms and neuroleptic malignant syndrome - Hirjak, Dusan; Sartorius, Alexander; Kubera, Katharina Maria; Wolf, Robert Christian (Der Nervenarzt, 2019)
In rare cases, pharmacotherapy in schizophrenic psychoses can be associated with life-threatening antipsychotic-induced movement disorders. The two most severe complications are antipsychotic-associated catatonic symptoms (ACS) and neuroleptic malignant syndrome (NMS). Although both constellations necessitate rapid medical care, the diagnosis is still a clinical challenge. Although there is no established treatment of ACS (here designated as a specific subtype of catatonic symptoms), an attempt should be made with benzodiazepines and memantine can also be helpful. In severe drug-refractory cases electroconvulsive therapy (ECT) can be indicated. The NMS represents a life-threatening constellation that frequently requires intensive care unit treatment. The medicinal treatment with benzodiazepines, bromocriptine, amantadine, dantrolene and/or ECT is also advocated. Finally, this review article also summarizes the currently available literature for treatment of genuine catatonic symptoms. In conclusion, the abovementioned clinical syndromes must be rapidly recognized and treated. Early recognition and treatment of these movement disorders can under certain circumstances be lifesaving and favorably influence the later clinical outcome.
Online publiziert: 20. August 2018
Gesehen am 18.07.2019